Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380029
|View full text |Cite
|
Sign up to set email alerts
|

Certified Robustness of Community Detection against Adversarial Structural Perturbation via Randomized Smoothing

Abstract: Community detection plays a key role in understanding graph structure. However, several recent studies showed that community detection is vulnerable to adversarial structural perturbation. In particular, via adding or removing a small number of carefully selected edges in a graph, an attacker can manipulate the detected communities. However, to the best of our knowledge, there are no studies on certifying robustness of community detection against such adversarial structural perturbation. In this work, we aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 30 publications
1
97
0
Order By: Relevance
“…Randomized smoothing: Randomized smoothing [4,10,19,24,25,27,28,32] is state-of-the-art technique to build provably robust machine learning. Compared with other certified defense mechanisms, randomized smoothing has two key advantages: 1) scalable to large neural networks, and 2) applicable to arbitrary classifiers.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized smoothing: Randomized smoothing [4,10,19,24,25,27,28,32] is state-of-the-art technique to build provably robust machine learning. Compared with other certified defense mechanisms, randomized smoothing has two key advantages: 1) scalable to large neural networks, and 2) applicable to arbitrary classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Cohen et al [10] derived the first tight certified robustness guarantee for randomized smoothing with Gaussian noise by Neyman-Pearson Lemma [36]. Jia et al [19] generalized the tight certified robustness guarantee to general toppredictions for randomized smoothing with Gaussian noise. Jia et al [20] leveraged randomized smoothing to certify robustness of community detection against structural perturbations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been research on providing a variety of defenses to adversarial examples. Some of it has shown qualified empirical success [40], some has provided certification guarantees about very specific adversaries [65] and some has even focused on top-k classification [32]. However, the adversarial examples research literature has also found that robust performance (on adversarial examples) often comes at the cost of clean performance (on regular test set examples) [30].…”
Section: Facial Search Service Countermeasures (Adaptive Privacy Adversaries)mentioning
confidence: 99%
“…This solution trades scalability with clean-data accuracy, which drops significantly as the allowed adversarial perturbation increases. In a similar vein, recent works prove the certified robustness of randomized smoothing, a pre-processing technique similar to Randomized Squeezing and Region-Based Classification which adds Gaussian noise to the classifier's input (instead of uniform noise) [9,22].…”
Section: Related Workmentioning
confidence: 99%